2020
DOI: 10.3390/cancers12051146
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and Validation of an Individualized Cell Cycle Process-Related Gene Signature to Predict Cancer-Specific Survival in Patients with Bladder Cancer

Abstract: More accurate models are essential to identify high-risk bladder cancer (BCa) patients who will benefit from adjuvant therapies and thus helpful to facilitate personalized management of BCa. Among various cancer-related hallmarks and pathways, cell cycle process (CCP) was identified as a dominant risk factor for cancer-specific survival (CSS) in BCa. Using a series of bioinformatic and statistical approaches, a CCP-related gene signature was established, and the prognostic value was validated in other independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…40 Recent studies indicate that cell cycle gene signatures show strong capacities of prognostication in many malignancies and have the potential of evaluating immunogenicity of tumors and their responses to ICIs. [41][42][43] However, such relationship between cell cycle signatures and tumor immune microenvironment (TIME) in ccRCC was not reported before. In present study, we built a gene signature included two cell cycle genes (FOXM1&TOP2A) adopting DEGs from GEO database.…”
Section: Discussionmentioning
confidence: 96%
“…40 Recent studies indicate that cell cycle gene signatures show strong capacities of prognostication in many malignancies and have the potential of evaluating immunogenicity of tumors and their responses to ICIs. [41][42][43] However, such relationship between cell cycle signatures and tumor immune microenvironment (TIME) in ccRCC was not reported before. In present study, we built a gene signature included two cell cycle genes (FOXM1&TOP2A) adopting DEGs from GEO database.…”
Section: Discussionmentioning
confidence: 96%
“…Advances in high-throughput techniques, such as microarray and RNA-sequencing (RNA-seq), together with well-established databases, such as the Cancer Genome Atlas (TCGA) and the public genomic data repository Gene Expression Omnibus (GEO), have uncovered new transcriptional landscapes, encouraging researchers to identify molecular markers for cancer diagnosis and prognosis [ 17 ]. Here, we performed RNA-seq analysis and identified BUB1 as a differentially expressed gene in NMIBC and normal adjacent tissue (NAT).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, numerous previous studies indicated that cell cycle gene signatures have the potential for evaluating immune cell infiltration, immune evasion, and immune responses (23)(24)(25). However, the relationship between cell cycle-related signatures and tumor immune situation in PRAD was not explored before.…”
Section: Discussionmentioning
confidence: 99%